RETRACTED: Climate change and energy policies in Shanghai: A multilevel governance perspective. (15th February 2016) - Francesch-Huidobro, Maria
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of the Editor-in-Chief, as the article shows significant overlap with the unpublished draft: "Governing Through Hierarchy: Climate Change Policy in Shanghai" by Thomas Richard Johnson.